Research of the Fatigue Characteristic of V-ribbed Belt - Li Guojun (Jixie chuandong, 2015)
To the problems of the belt is easy to produce such as fatigue failure and fracture in belt transmission process,with the V-ribbed belt of belt drive system as research object,the V-ribbed belt rubber physical properties is got by the experiment,and the material characteristic getting from the experimental is substituted into the ABAQUS of finite element analysis software to carry out the simulation analysis on the fatigue characteristic of V-ribbed belt.The analysis results show that with the increase of the load,the unit length tensile resistance of V-ribbed belt is increasing and the cycles index are decreases,and with the increase of initial crack size,the unit length tensile resistance of v-ribbed belt is increasing and the increasing rate is reduced,and the cycles index display the trends of first slowly decreases then sharply reduced.With the increase of displacement,the unit length tensile resistance of v-ribbed belt is increasing,and the cycles index are reduced.